THE UTILIZATION OF BAMBOO ACTIVATED CARBON, INDRAYANTI BEACH ACTIVATED SAND, AND KRASAK RIVER ACTIVATED GRAVEL AS ABSORBENT ON PROCESS OF LPPMP UNY WATER PURIFICATION FOR DRINKING WATER - Widiastuti Tri Widiastuti; Suparno Suparno (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2016)
The aims of this research are to understand (1) the influence of volume and types of absorbent (bamboo activated carbon, Indrayanti beach activated sand, and Krasak river activated gravel) on light transmission efficiency (TE), TDS, and pH on LPPMP UNY water purification. (2) The influence of absorbent kinds on the absorption efficiency of Fe on LPPMP UNY water purification. (3) The influence of the absorbents composition variation on light transmission efficiency, TDS, pH, and the absorption efficiency of Fe on LPPMP UNY water purification. (4) The influence of the FAS (Filtration, Absorption, and Sedimentation) system absorption capacity on the decreases of the amount of coliform on LPPMP UNY water purification. First process of this research is carbonization of bamboo, crushing, sieving, washing, drying, and physics activation by oven heating at temperature of 200 oC for 1 hour. The second step is filtration, absorption, and sedimentation using a variation of the volume of each absorbent and volume ratio of absorbent kind composition are placed in the FAS pipe. The next step is the measurement of light transmission intensity, total dissolved solid, temperature, pH in all filtering water samples, and the measurement Fe and total coliform in given samples. The result of this research indicated that light transmission efficiency in the activated carbon, activated sand, and activated gravel on the water purification particles tends to increase, while TDS tends to decrease, and there was no cange on pH. The absorption efficiency of Fe best fit to the bamboo active carbon (90,3±0,2) %. The highest light transmission intensity could be found at the ratio of K:K:P:P (90±1) %. The TDS reach its best at the ratio K:K:Kr:Kr 141 ppm. The best absorption efficiency of Fe is at the ratio of K:K:P:P and K:K:Kr:Kr (90,3±0,2) %. The amount of coliform decreases to 0 MPN/100ml in 2450 ml sample.Keywords: absorbent, active carbon, light tranmission intensity, Fe, and coliform